Colorectal cancer in patients with single versus double positive faecal immunochemical test results: A retrospective cohort study from a public tertiary hospital. - Tian Zhi Lim; Jerrald Lau; Gretel Jianlin Wong; Ker-Kan Tan (PLoS ONE, 2021)
Background Screening for colorectal cancer (CRC) using the faecal immunochemical test (FIT) is widely advocated. Few studies have compared the rate of detecting colonoscopic pathologies in single compared to double FIT-positive follow-up colonoscopy-compliant individuals in a two-sample national FIT screening program. Objective To compare CRC incidence in double FIT-positive versus single FIT-positive individuals using a retrospective cohort of patients from a tertiary hospital in Singapore. Design Retrospective cohort study. Setting Data was extracted from one public tertiary hospital in Singapore. Participants 1,422 FIT-positive individuals from the national FIT screening program who were referred to the hospital from 1st January 2017 to 31st March 2020 for follow-up consultation and diagnostic colonoscopy. Measurements The exposure of interest was a positive result on both FIT kits. The main outcome was a follow-up diagnostic colonoscopy finding of CRC. The secondary outcome was a diagnostic colonoscopy finding of a colorectal polyp. Results Incidence density of CRC was 1.15 and 13.10 per 100,000 person-months, in the single and double FIT-positive group, respectively. This resulted in an incidence rate ratio of 11.40 (95% CI = 4.34, 35.09). Colorectal polyp detection was significantly higher (p < 0.01) in the double (103 of 173 participants; 59.5%) compared to the single (279 of 671 participants; 41.6%) FIT-positive group. Limitations The key limitation of this study was the relatively small cohort derived from a single tertiary hospital, as this had the effect of limiting the number of incident cases, resulting in comparatively imprecise CIs. Conclusions Double FIT-positive individuals are significantly more likely to have a colonoscopy finding of incident CRC or premalignant polyp than single FIT-positive individuals. Clinicians and policymakers should consider updating their CRC screening protocols accordingly.